ANALISIS SENSITIVITAS NBIAYA PAKAN TERNAK AYAM RAS PETELUR (STUDI KASUS PT. ROSE FARM DI DESA CANDIBINANGUN KECAMATAN PAKEM KABUPATEN SLEMAN PROVINSI DIY) - Ni Made Suyastiri YP; Indah Widowati; Indri Ariani Martwardja (Jurnal Dinamika Sosial Ekonomi, 2010)
The analysis of sensitivity Food Cost Chiken Livestock of Farm (The case study on PT. Rosa Farm at Candibinangun District of Pakem Sub-Province of Sleman Province DIY). The chicken company becomes an attractive and profitable in future, in which chicken livestock has classfication as good layer and fresh chicken. The research aimed to know how far the influence of increasing chicken food cost to chicken livestock poultry company if the increasing were 5% and the influence of chicken food cost to the overall profit of chicken live stock of farm and influence of chicken food cost the production of chicken poultry at PT Rosa Farm. Method which used in this research is case study method on PT Rosa Farm located at Countryside of Candibinangun, Distict of Pakem, Sub-Province Sleman. The result shown that the increasing of chicke nfood cost have a significant influence to the production cost, especially in the chicken food cost. The hypothesis test for the first used with sensitivity Analysis, the second test used with Simple Linear Regression Analisis.Key Words : Sensitivity Chicken food cost, Egg production